2020
DOI: 10.3389/fnins.2020.00078
|View full text |Cite
|
Sign up to set email alerts
|

NBOMes–Highly Potent and Toxic Alternatives of LSD

Abstract: Recently, a new class of psychedelic compounds named NBOMe (or 25X-NBOMe) has appeared on the illegal drug market. NBOMes are analogs of the 2C family of phenethylamine drugs, originally synthesized by Alexander Shulgin, that contain a N-(2-methoxy)benzyl substituent. The most frequently reported drugs from this group are 25I-NBOMe, 25B-NBOMe, and 25C-NBOMe. NBOMe compounds are ultrapotent and highly efficacious agonists of serotonin 5-HT 2A and 5-HT 2C receptors (Ki values in low nanomolar range) with more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 109 publications
0
56
0
1
Order By: Relevance
“…Indeed, even in our case, 2C-B and 25B-NBOMe were found to be stronger genotoxic agents than 2C-I and 2C-H. 25X-NBOMe compounds are ultrapotent and highly efficacious agonists of serotonin 5-HT 2A and 5-HT 2C receptors (Ki values in low nanomolar range), with more than 1000-fold selectivity for 5-HT 2A compared with 5-HT 1A , and they have higher selectivity and affinity for the serotonin 5-HT 2A receptor than their corresponding compounds of the 2C-X series [ 7 , 50 , 51 ]. This pharmacokinetic profile is reflected in their more potent in vitro activity and psychedelic and even toxic in vivo effect [ 23 , 52 , 53 , 54 ]. In vitro studies have shown that 25X-NBOMe have greater potency on 5HT 2A receptors (EC50 = 0.758–0.819 nM) than 2C-X compounds (EC50 = 3.16–8.46 nM) [ 55 ], and this agrees with the in vivo studies showing that 25X-NBOMe induced a head twitch response in rodents (HTR; a behavioral marker in rodents for hallucinogen effects in humans) with a potency several-fold higher than their 2C-X counterparts [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, even in our case, 2C-B and 25B-NBOMe were found to be stronger genotoxic agents than 2C-I and 2C-H. 25X-NBOMe compounds are ultrapotent and highly efficacious agonists of serotonin 5-HT 2A and 5-HT 2C receptors (Ki values in low nanomolar range), with more than 1000-fold selectivity for 5-HT 2A compared with 5-HT 1A , and they have higher selectivity and affinity for the serotonin 5-HT 2A receptor than their corresponding compounds of the 2C-X series [ 7 , 50 , 51 ]. This pharmacokinetic profile is reflected in their more potent in vitro activity and psychedelic and even toxic in vivo effect [ 23 , 52 , 53 , 54 ]. In vitro studies have shown that 25X-NBOMe have greater potency on 5HT 2A receptors (EC50 = 0.758–0.819 nM) than 2C-X compounds (EC50 = 3.16–8.46 nM) [ 55 ], and this agrees with the in vivo studies showing that 25X-NBOMe induced a head twitch response in rodents (HTR; a behavioral marker in rodents for hallucinogen effects in humans) with a potency several-fold higher than their 2C-X counterparts [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These preclinical studies are in agreement with the dosages used by consumers. In fact, the active dosages of 25X-NBOMe range from 20 to 100 times lower than those of the compounds of the class 2C-X [ 23 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysergic acid diethylamide (LSD) and other synthetic “designer” psychedelic drugs with serotonergic properties (phenethylamine analogs or “N-Bombs”, mescaline), may produce hyperthermia along with other effects on the autonomic nervous system [ 57 - 60 ]. Patients typically experience hallucinations, agitation and tachycardia, but occasionally may develop a more severe syndrome of psychosis, catatonic stupor, hyperactivity or rigidity, rhabdomyolysis, and sympathetic activation leading to hyperthermia, coagulopathies, respiratory arrest, and coma.…”
Section: Hyperthermic Syndromesmentioning
confidence: 99%
“…In addition to LSD, other drugs with halucinogenic effects, such as N-benzylsubstituted phenethylamines (NBOMes), are also available in blotters and are widely consumed in recent years, being commonly confused with LSD 10,12 . Due to this similarity, the correct identification of the seized drug is extremely important.…”
Section: Introductionmentioning
confidence: 99%